2007
DOI: 10.1007/s00792-007-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses and metal tolerance of Chlamydomonas acidophila in metal-enriched lake water and artificial medium

Abstract: Chlamydomonas acidophila faces high heavy-metal concentrations in acidic mining lakes, where it is a dominant phytoplankton species. To investigate the importance of metals to C. acidophila in these lakes, we examined the response of growth, photosynthesis, cell structure, heat-shock protein (Hsp) accumulation, and metal adsorption after incubation in metal-rich lake water and artificial growth medium enriched with metals (Fe, Zn). Incubation in both metal-rich lake water and medium caused large decreases in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 69 publications
4
31
0
Order By: Relevance
“…Similar results were found in C. reinhardtii in the presence of cadmium and copper (Boswell et al, 2002;Gillet et al, 2006), as well as in other photosynthetic organisms (Takamura et al, 1989;Wang et al, 2004). Although growth in extreme acidic environments is expected to require specific cellular adaptations of photosynthetic organisms, other studies have reported stress symptoms in acidophilic Chlamydomonas growing under acidic or metal-enriched natural water (Spijkerman et al, 2007;Langner et al, 2009). On the contrary, phytochrome B, phosphoribulokinase and phosphoglycerate kinase were up-regulated when cells were grown in metal rich acidic water .…”
Section: Acidic Environments the Río Tinto (Sw Spain) Casesupporting
confidence: 71%
See 3 more Smart Citations
“…Similar results were found in C. reinhardtii in the presence of cadmium and copper (Boswell et al, 2002;Gillet et al, 2006), as well as in other photosynthetic organisms (Takamura et al, 1989;Wang et al, 2004). Although growth in extreme acidic environments is expected to require specific cellular adaptations of photosynthetic organisms, other studies have reported stress symptoms in acidophilic Chlamydomonas growing under acidic or metal-enriched natural water (Spijkerman et al, 2007;Langner et al, 2009). On the contrary, phytochrome B, phosphoribulokinase and phosphoglycerate kinase were up-regulated when cells were grown in metal rich acidic water .…”
Section: Acidic Environments the Río Tinto (Sw Spain) Casesupporting
confidence: 71%
“…In our case, this cannot be the reason, since phototrophic biofilms are the principal contributors of biomass www.intechopen.com in Río Tinto, representing over 65% of the total biomass (Lopez-Archilla et al, 2001). Another suggested reason for the low productivity in these extreme environments could be the lack of nutrients such as ammonium, phosphate or nitrate (Spijkerman et al, 2007). All the photosynthetic parameters analyzed showed statistical significant differences among species and sampling locations.…”
Section: Acidic Environments the Río Tinto (Sw Spain) Casementioning
confidence: 96%
See 2 more Smart Citations
“…This stenoecious, specialist species (Gerloff-Elias et al 2005, Spijkerman et al 2007 has been recorded from AML and extremely acid rivers (pH ;2) in Europe and from different environments on other continents (Amaral Zettler et al 2002, Gerloff-Elias et al 2005; (2) two closely related, but different flagellate species, Ochromonas spp., the dominant bacterivore in these mining lakes accounting for the consumption of up to 90% of the daily bacterial production (Schmidtke et al 2006), and (3) two ciliate species of the genus Oxytricha that were isolated from two similar, but geographically distant AML in Austria and Germany. Oxytricha is the only ciliate genus encountered in all our study lakes (T. Weisse et al, unpublished manuscript).…”
Section: Introductionmentioning
confidence: 99%